Treatment of climacteric symptoms in survivors of gynaecological cancer. Issue 3 (November 2015) - Biglia, Nicoletta; Bounous, Valentina Elisabetta; Sgro, Luca Giuseppe; D'Alonzo, Marta; Gallo, Martina
Highlights: Physicians are reluctant in prescribing HRTin gynaecological cancer survivors because of the fear that hormones may influence the risk of recurrence. No evidence of increased risk in the available studies on HRT in survivors of endometrial, ovarian and squamous cervical cancer, even if no definitive results have been formulated. The positive effect of HRT on the quality of life seems to outweigh the unfounded suspicion about an increased risk of recurrence. It is mandatory to inform patients about alternative therapies other than estrogens, in particular for prevention of osteoporosis and cardiovascular disease. Abstract: Different treatments (surgery, radiotherapy, chemotherapy) for gynaecological cancers may cause ovarian failure or increase menopausal symptoms. There is a widespread reluctance among physicians to prescribe hormone replacement therapy (HRT) to the survivors of gynaecological cancer. This review analyses the use of HRT and of alternative therapies in such women. Squamous cervical cancer is not estrogen dependent and thus HRT is not contraindicated. While a cautious approach to hormone-dependent cancer is warranted, for women treated for non-hormone-related tumours alternative treatments for menopausal symptoms should be given due consideration, as any reluctance to prescribe HRT for them has neither a biological nor a clinical basis. In studies of HRT for survivors of endometrial and ovarian cancer, for instance, no evidence of increased risk was found, although no definitive conclusions can yet be formulated. The positive effect of HRT on quality of life seems to outweigh the unfounded suspicion of an increased risk of recurrence of non-hormone-related tumours. Effective non-hormonal alternatives for vasomotor symptoms are selective serotonin reuptake inhibitors and selective serotonin–norepinephrine reuptake inhibitors.